Hafnium(IV) Chloride Catalyzes Highly Efficient Acetalization of Carbonyl Compounds - Bonilla-Landa, Israel; López-Hernández, Emizael; Barrera-Méndez, Felipe; Salas, Nadia C.; Olivares-Romero, José L. (Current Organic Synthesis, 2019)
Background: Hafnium(IV) tetrachloride efficiently catalyzes the protection of a variety of aldehydes and ketones, including benzophenone, acetophenone, and cyclohexanone, to the corresponding dimethyl acetals and 1,3-dioxolanes, under microwave heating. Substrates possessing acid-labile protecting groups (TBDPS and Boc) chemoselectively generated the corresponding acetal/ketal in excellent yields. Aims and Objectives: In this study. the selective protection of aldehydes and ketones using a Hafnium(IV) chloride, which is a novel catalyst, under microwave heating was observed. Hence, it is imperative to find suitable conditions to promote the protection reaction in high yields and short reaction times. This study was undertaken not only to find a novel catalyst but also to perform the reaction with substrates bearing acid-labile protecting groups, and study the more challenging ketones as benzophenone. Materials and Methods: Using a microwave synthesis reactor Monowave 400 of Anton Paar, the protection reaction was performed on a raging temperature of 100°C ±1, a pressure of 2.9 bar, and an electric power of 50 W. More than 40 substrates have been screened and protected, not only the aldehydes were protected in high yields but also the more challenging ketones such as benzophenone were protected. All the products were purified by simple flash column chromatography, using silica gel and hexanes/ethyl acetate (90:10) as eluents. Finally, the protected substrates were characterized by NMR 1H, 13C and APCI-HRMS-QTOF. Results: Preliminary screening allowed us to find that 5 mol % of the catalyst is enough to furnish the protected aldehyde or ketone in up to 99% yield. Also it was found that substrates with a variety of substitutions on the aromatic ring (aldehyde or ketone), that include electron-withdrawing and electrondonating group, can be protected using this methodology in high yields. The more challenging cyclic ketones were also protected in up to 86% yield. It was found that trimethyl orthoformate is a very good additive to obtain the protected acetophenone. Finally, the protection of aldehydes with sensitive functional groups was performed. Indeed, it was found that substrates bearing acid labile groups such as Boc and TBDPS, chemoselectively generated the corresponding acetal/ketal compound while keeping the protective groups intact in up to 73% yield. Conclusion: Hafnium(IV) chloride as a catalyst provides a simple, highly efficient, and general chemoselective methodology for the protection of a variety of structurally diverse aldehydes and ketones. The major advantages offered by this method are: high yields, low catalyst loading, air-stability, and non-toxicity.
Keywords: microwave reaction